Cross-continental collaboration for understanding postpartum major depression with psychotic features - Kimmel, Mary; Thippeswamy, Harish; Kamperman, Astrid; Madhuri, H. N.; Putnam, Karen; Schiller, Crystal; Weinel, Katie; Rackers, Hannah; Gilden, Janneke; Bergink, Veerle; Meltzer-Brody, Samantha; Chandra, Prabha (Frontiers in Global Women's Health, 2022)
Purpose Assess postpartum depression and psychotic symptoms from three continents. Methods Compare numbers of women with depression and psychotic symptoms, mania with or without psychotic features, or transient non-affective psychosis and medication choice. Results The prevalence of postpartum depression and psychosis and treatment choice differed at each site. Conclusions Best treatment for postpartum depression with psychotic features has not been established yet. Cross-continental collaboration with similar assessments holds promise to develop best practices for these high risk mother-infant dyads.